Evaluation of antibiotic escalation in response to nurse-driven inpatient sepsis screen. Issue 1 (3rd December 2021) - Furukawa, Daisuke; Dieringer, Thomas D.; Wong, Mitchell D.; Tong, Julia T.; Cader, Isa A.; Wisk, Lauren E.; Han, Maria A.; Gupta, Summer M.; Kerbel, Russell B.; Uslan, Daniel Z.; Graber, Christopher J.
Abstract: Objective: To determine the frequency and predictors of antibiotic escalation in response to the inpatient sepsis screen at our institution. Design: Retrospective cohort study. Setting: Two affiliated academic medical centers in Los Angeles, California. Patients: Hospitalized patients aged 18 years and older who had their first positive sepsis screen between January 1, 2019, and December 31, 2019, on acute-care wards. Methods: We described the rate and etiology of antibiotic escalation, and we conducted multivariable regression analyses of predictors of antibiotic escalation. Results: Of the 576 cases with a positive sepsis screen, antibiotic escalation occurred in 131 cases (22.7%). New infection was the most documented etiology of escalation, with 76 cases (13.2%), followed by known pre-existing infection, with 26 cases (4.5%). Antibiotics were continued past 3 days in 17 cases (3.0%) in which new or existing infection was not apparent. Abnormal temperature (adjusted odds ratio [aOR], 3.00; 95% confidence interval [CI], 1.91–4.70) and abnormal lactate (aOR, 2.04; 95% CI, 1.28–3.27) were significant predictors of antibiotic escalation. The patient already being on antibiotics (aOR, 0.54; 95% CI, 0.34–0.89) and the positive screen occurred during a nursing shift change (aOR, 0.36; 95% CI, 0.22–0.57) were negative predictors. Pneumonia was the most documented new infection, but only 19 (50%) of 38 pneumonia cases met full clinical diagnostic criteria. Conclusions: Inpatient sepsis screening led to a new infectious diagnosis in 13.2% of all positive sepsis screens, and the risk of prolonged antibiotic exposure without a clear infectious source was low. Pneumonia diagnostics and lactate testing are potential targets for future stewardship efforts.